Gastric Mucosa Plasma Cells is Unspecific for Diagnosing Helicobacter pylori Infection - Gilda Hartecia; Willy Sandhika; Ummi Maimunah; Muhammad Miftahussurur (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Background: A high density of Helicobacter pylori is believed to trigger an accumulation of plasma cells in the gastric mucosa. This accumulation stimulated the production of antibodies, causing high antibodies titer being circulated in the blood. The aims of this study is to identify the correlation between the number of plasma cells and H. pylori density in gastric mucosa.Method: This observational analytic study was performed with cross-sectional approach. The samples were the paraffin blocks which consisted of endoscopic gastric biopsy tissues of chronic gastritis patient in Anatomic Pathology Laboratory Dr. Soetomo General Hospital Surabaya in 2017 period. A total of 30 samples were purposively collected. Endoscopic gastric biopsy tissues were stained by two stains, Haematoxylin-Eosin and Modified Giemsa. The examination was performed by experienced pathologist. The correlation between total plasma cells and H. pylori density in gastric mucosa and the difference of total plasma cells between gastric mucosae with different density of H. pylori were determined.Results: There was no significant correlation between total plasma cells and H. pylori density in gastric mucosa. And there was no significant difference of the number of plasma cells found with different density of H. pylori.Conclusion: The number of plasma cells in the gastric mucosa is unspecific for diagnosing H. pylori infection. Other causes associated with plasma cells need to be assessed in further studies.